The prevalence and risk of DSM‐IV axis I disorder in adults with early‐life earthquake stress: A cross‐sectional study. Issue 76 (20th June 2019) - Song, Mei; Wang, Lan; Zhao, Xiao‐Chuan; Li, Na; Wang, Ran; Gao, Yuan‐Yuan; Yu, Lu‐Lu; An, Cui‐Xia; Wang, Xue‐Yi
Abstract : Objectives: Tangshan earthquake which had a magnitude of 7.8 killed approximately 250, 000 people in China in 1976. In the present study, we sought to determine the prevalence and risks of mental disorders in adults who experienced earthquake as an infant or in the prenatal period. Methods: This cross‐sectional cohort study recruited participants based on the urban resident registry of Tangshan, Hebei province, 2013 using a multistage stratified cluster sampling method with selection probabilities proportional to size. We recruited subjects who were born between July 29, 1975 and April 28, 1978 that was one year before and 1.9 years after the occurrence of Tangshan Earthquake, respectively. Current psychiatric diagnoses and lifetime psychiatric diagnoses were obtained through the Structured Clinical Interview for DSM‐IV Axis I Disorders Patient Research Version. Unconditional logistic regression analysis was performed to analyze risk factors of mental disorders. Results: Totally1380 subjects were included with 392 subjects exposed to the earthquake in the fetal period, 399 subjects who experienced the earthquake during their infancy, and 589 subjects who had no exposure to the earthquake. Twenty‐one (2.7%; current 1.9%) subjects exposed to earthquake were diagnosed with major depressive disorder versus 2.3% (current 1.5%) in the non‐exposure group. Five (0.6%; current 0.6%) subjects with exposure to earthquake had bipolar disorder versus 0.9% in the non‐exposure group.Thirteen (1.6%; current 1.6%) subjects with exposure to earthquake had schizophrenia versus 0.2% in the non‐exposure group ( P= 0.006). Furthermore, 5.2% (current 3.7%) subjects with exposure to earthquake had anxiety disorders versus 5.7% (current 3.9%) in the non‐exposure group. Moreover, 8.1% (current 7.0%)subjects with exposure to earthquake had alcohol use disorders versus 7.1% (current 5.3%) in the non‐exposure group. Furthermore, the prevalence of schizophrenia of the prenatal exposure group (2.3%) was significantly higher than the other two groups ( χ 2  = 10.273, P  = 0.006); however, no statistically significant difference was found in the current and lifetime prevalence of other DSM‐IV axis I disorders among the three groups ( P  > 0.05). Our multivariate regression analysis showed that prenatal earthquake stress exposure was not a significant risk of any of the lifetime or current DSD‐IV axis I disorders. Conclusion: Adults who were exposed to earthquake in the prenatal period had a significantly higher rate of schizophrenia than those who were not exposed or who experienced earthquake in their infancy. No statistically significant difference was found in the current and lifetime prevalence of other DSM‐IV axis I disorders between those exposed and those not exposed to earthquake. Furthermore, prenatal earthquake stress exposure was not a significant risk of any of the lifetime or current DSD‐IV axis I disorders.